Training on Flying Fish Egg Processing to Increase Household Income - Dedi Harianto; Andi Sawe Ri Esso; Supratman Tajuddin (PT. Global Research Collaboration, 2024)
The Community Partnership Program (PKM) is implemented in Village Kalukuang, Galesong District, Takalar Regency, South Sulawesi Province. This initiative is motivated by several issues, primarily the limited capacity of housewives to develop the processing of flying fish eggs, which affects their income. The challenges are rooted in three aspects: (1) a lack of knowledge and skills in managing flying fish eggs, (2) insufficient access to marketing opportunities, and (3) the non involvement of local government. These limitations significantly impact household income derived from processing flying fish eggs. To address this issue, it is essential to expand knowledge and enhance skills, thereby improving these constraints through training, knowledge-sharing, and skill development. The methods employed to resolve these problems include mentoring, discussions, and question and answer sessions.